LIQUID LAYERS MOTION INVESTIGATION - Victor V. Trepachev (Advanced Engineering Research)
The diffraction motion of two layers of the incompressible heavy liquid around the vertical circular support column is investigated. The hard cover approaching is used to distinguish internal wave alone. The research data are extended to the utmost scope of the wave motion of the liquid layers of both the field studies and lab tests.